Two-component hybrid gel as well as preparation method and application thereof
By introducing a coupling agent containing active groups into the two-component hybrid glue of MS resin and epoxy resin to promote chemical cross-linking, the problem that the two-component hybrid glue in the existing technology powders under high temperature and high humidity environment is solved. to solve the problem and achieve improvements in mechanical properties and aging resistance.
Patent Information
- Application Number
- CN202411486180.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-20
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-21
AI Technical Summary
The two-component hybrid glues of existing MS resins and epoxy resins are easily powdered under high temperature and high humidity environments, resulting in bonding failure, and the production process is cumbersome and costly.
By introducing the coupling agent containing at least two active groups, it promotes chemical cross -linking between MS resin and epoxy resin, forms a stable chemical bond, and improves mechanical properties and aging resistance.
It significantly improves the mechanical performance and aging resistance of dual -component hybridization, reduces the performance of performance under high humidity and heat conditions, avoids the problem of powderization, and maintains a good bonding effect.
Smart Images

Figure CN119331556A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a two-component hybrid glue and a preparation method and application thereof. Background Art
[0002] The two-component hybrid adhesive of MS resin and epoxy resin can maintain the flexibility of MS resin while taking into account the high strength of epoxy resin, and is widely used in the fields of automobile, electrical appliances, and electronics. However, the aging resistance of the two-component hybrid adhesive is poor. When the two-component hybrid adhesive of MS resin and epoxy resin is applied to the back adhesive of building panels (such as rock panels, tiles, etc.), since the preparation process of the two-component hybrid adhesive is a physical blending, no effective chemical bond is formed between the two components, so after passing through the harsh environment of high temperature and high humidity, powdering problems will occur, causing bonding failure. This results in the application field of the two-component hybrid adhesive of MS resin and epoxy resin being limited.
[0003] In order to improve the aging resistance of the two-component hybrid adhesive of MS resin and epoxy resin, the prior art improves the compatibility of the system by modifying the calcium carbonate filler therein, and introduces antioxidant groups to improve its aging resistance. However, this method does not solve the problem that no effective chemical bond is formed between the MS resin and the epoxy resin, and since the filler needs to be modified, it is necessary to add filler modification process equipment to the existing normal production equipment during the production process, which makes the production process cumbersome and the production cost high. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a two-component hybrid adhesive, which forms an effective chemical crosslinking between the MS resin component and the epoxy resin component by introducing a specific coupling agent, thereby improving the mechanical properties and aging resistance of the two-component hybrid adhesive and reducing the impact of the environment on the material under high humidity and heat conditions.
[0005] The second aspect of the present invention is to provide a method for preparing a two-component hybrid glue.
[0006] A third aspect of the present invention is to provide an adhesive.
[0007] A fourth aspect of the present invention is to provide an application of a two-component hybrid glue or adhesive.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The first aspect of the present invention provides a two-component hybrid glue, comprising component A and component B;
[0010] The component A comprises a silane-modified polyether resin, a first coupling agent, an antioxidant, a first auxiliary agent, and a first inorganic filler;
[0011] The B component includes epoxy resin, a second coupling agent, a second auxiliary agent, and a second inorganic filler;
[0012] The first coupling agent has at least two active groups in its structure; the active groups include groups that can react with methoxy, ethoxy, epoxy or hydroxyl groups; the antioxidant includes hindered phenol antioxidants; the amount of the first coupling agent is 5 to 10% of the mass of the epoxy resin; the amount of the antioxidant is 1 to 4% of the total mass of the silane-modified polyether resin and the epoxy resin.
[0013] MS resin (silane modified polyether resin) and epoxy resin are two materials with different properties. MS resin has high flexibility but low overall strength, while epoxy resin has high hardness but poor flexibility. After the two are hybridized, due to the poor compatibility of MS resin and epoxy resin, and the hybridization of the two is a physical blending, effective chemical crosslinking cannot be formed. This blending not only leads to low mechanical properties of the two-component hybrid adhesive after curing, but also under high humidity and heat conditions, the performance is prone to obvious degradation. In severe cases, the material may even powder and lose the bonding effect.
[0014] The present invention realizes chemical crosslinking of MS resin and epoxy resin by introducing a coupling agent containing at least two active groups, thereby improving the mechanical properties and aging resistance of the material and enhancing the stability of the material. The main groups in MS resin and epoxy resin are methoxy or ethoxy, epoxy and hydroxyl groups generated during the crosslinking process, and the coupling agent selected in the present invention contains active groups, which can react chemically with these groups to form chemical bonds, so that component A containing MS resin and component B containing epoxy resin form chemical crosslinking to a certain extent, thereby improving the performance of the two-component hybrid adhesive.
[0015] At the same time, the dosage of the first coupling agent and antioxidant needs to be strictly controlled. When the dosage of the first coupling agent is less than 5%, the chemical bonds that can be formed are limited, the mechanical properties are reduced, and the aging resistance is not good; when the dosage is higher than 10%, due to the excessive number of active groups, it is impossible to form a polymer that meets the requirements. At the same time, the coupling agent is a small molecule. There are too many small molecules in the system and they cannot participate in the reaction, which can be equivalent to excessive diluent dosage. At this time, the mechanical properties are significantly reduced. When the dosage of the antioxidant is less than 1%, the aging resistance of the two-component hybrid glue is relatively poor; when the dosage of the antioxidant is higher than 4%, since the antioxidants used are all powders and require high temperature to dissolve when used, excessive addition will affect production efficiency and reduce the initial mechanical properties of the two-component hybrid glue to a certain extent.
[0016] Preferably, the mass ratio of the component A to the component B is (1-5):1.
[0017] More preferably, the mass ratio of the component A to the component B is (1-2):1.
[0018] Preferably, the first coupling agent contains 2 to 3 amino groups in its structure.
[0019] Common coupling agents on the market include monoaminotrialkoxy coupling agents, etc. Since MS resin contains more alkoxy groups at both ends, the degree of chemical bond crosslinking that can be formed by monoamino coupling agents is not ideal. Compared with monoamino coupling agents, diamino and triamino coupling agents contain two or three amino groups in their structure, which can provide more groups that can form chemical bond crosslinking with epoxy resin, so the effect achieved by diamino and triamino coupling agents is more ideal. This is because although in theory the amino group of a monoamino coupling agent can only react with one epoxy group, in fact, due to steric hindrance, the monoamino coupling agent may not be able to react with the group of the epoxy resin, that is, in fact, the amino group and epoxy group in the monoamino coupling agent do not react 1:1. Therefore, even if diamino and triamino coupling agents are affected by steric hindrance, because there are enough amino groups in the structure, the probability of reacting with epoxy groups is better and the effect is higher. Therefore, in actual use, the chemical bond crosslinking that diamino and triamino can produce is significantly better than that of monoamino coupling agents.
[0020] More preferably, the aminosilane coupling agent includes one or more of Dynasylan 1146, Dynasylan SIVO203, Dynasylan TRIAMO and Dynasylan DAMO-M of Evonik.
[0021] Preferably, the second coupling agent includes an epoxy-containing silane coupling agent.
[0022] More preferably, the second coupling agent is a silane coupling agent containing a glycidyl ether group or a glycidyloxy group.
[0023] More preferably, the second coupling agent includes one or more of Japan Shin-Etsu KBM-403, Momentive A-187, Dow Corning Z-6040, and Hubei New Blue Sky LT-560.
[0024] Preferably, the first coupling agent is used in an amount of 6-7% of the mass of the epoxy resin.
[0025] Preferably, the hindered phenol antioxidant contains alkylated bisphenol or polyphenol in its structure.
[0026] The preferred antioxidant of the present invention is an antioxidant of alkylated polyphenol type. MS resin and epoxy resin are both macromolecular polymers. The essence of their aging is that the internal structure of the macromolecular polymer has changed. It is an auto-oxidation reaction with free radical chain oxidation mechanism and auto-catalytic characteristics. Macromolecular polymers have specific molecular structures, and relatively weak bonds or defects exist in some structural parts, which are the entry points for macromolecular material aging. Alkylated polyphenol type antioxidants can prevent the destructive effect of free radicals in polymers by coupling reaction (i.e. termination reaction) or by giving a hydrogen atom, and play an anti-aging effect.
[0027] Common aromatic amine antioxidants and auxiliary antioxidants on the market each have their own disadvantages. For example, aromatic amine antioxidants have discoloration and pollution; auxiliary antioxidants have poor effects. Hindered phenol antioxidants include alkyl monophenols, alkylated polyphenols, etc. Among them, alkyl monophenols have high volatility and extractability, which will affect the antioxidant effect; while alkylated polyphenols have low volatility, are resistant to heat, water and solvent extraction, have good compatibility with most polymers, and have better antioxidant effects.
[0028] More preferably, the antioxidant includes one or more of BASF antioxidant 1010, antioxidant 2246, and antioxidant B225.
[0029] Preferably, the amount of the antioxidant in the component A is 1-2% of the total mass of the silane-modified polyether resin and the epoxy resin.
[0030] Preferably, the silane-modified polyether resin comprises a silane-modified polyether resin terminated with a dialkoxy group or a monoalkoxy group.
[0031] Preferably, the viscosity of the silane-modified polyether resin at 25° C. is 6000 to 50000 mPa·s.
[0032] More preferably, the silane-modified polyether resin includes one or more of SAX260, SAX350, SAX400, SAX510, SAX520, SAX530, SAX580, SAX750, S303H, S203H, and S327 produced by Kaneka.
[0033] Preferably, the epoxy resin includes bisphenol A epoxy resin and / or bisphenol F epoxy resin.
[0034] Preferably, the epoxy equivalent of the epoxy resin is 160 to 210 g / eq; and the viscosity of the epoxy resin at 25° C. is 2000 to 15000 cps.
[0035] More preferably, the epoxy resin includes one or more of China Taiwan Changchun BE-188, Nan Ya NPEL128, and Hongchang GELR-128.
[0036] The two ends of the molecular chain of silane-modified polyether resin (MS resin) are mainly methoxy or ethoxy groups, which react with water in the air under the action of a catalyst to generate hydroxyl groups, methanol or ethanol. The hydroxyl group can continue to react with the methoxy or ethoxy group of the MS resin to form a network crosslink. The epoxy resin, on the other hand, opens the epoxy group to generate hydroxyl groups under the action of a catalyst, and continues to react with the epoxy group to self-crosslink. Although both generate hydroxyl groups during the reaction, due to steric hindrance, the reactive groups cannot form an ideal chemical crosslinking state, and there are many groups in the system that cannot react normally due to steric hindrance, and cannot form stable chemical bonds. The present invention can solve this problem by introducing an amino-containing coupling agent.
[0037] Preferably, the first auxiliary agent includes at least one of a diluent, a plasticizer, an epoxy catalyst, a water scavenger, and a thixotropic agent.
[0038] Preferably, the second auxiliary agent includes at least one of a plasticizer, a MS catalyst, a water scavenger, carbon black, and a thixotropic agent.
[0039] Preferably, the inorganic filler includes heavy calcium carbonate and / or nano calcium carbonate.
[0040] More preferably, the diluent comprises a reactive diluent; both ends of the diluent contain alkoxy-terminated silane-modified polyether; and the viscosity of the diluent at 25° C. is 600 to 3000 cps.
[0041] More preferably, the diluent includes at least one of SAT010 and SAT145 produced by Kaneka.
[0042] Preferably, the epoxy catalyst comprises a tertiary amine catalyst.
[0043] More preferably, the epoxide catalyst comprises DMP-30.
[0044] Preferably, the MS catalyst comprises a chelated tin catalyst.
[0045] More preferably, the MS catalyst includes at least one of Nitto Kasei U-220H, U-303, U-200, U-28, and German TIB KAT-417.
[0046] Preferably, the mesh number of the carbon black is less than 325 meshes and the moisture content is ≤1%.
[0047] More preferably, the carbon black includes Cabot MONARCH 430 and / or Mitsubishi MA100.
[0048] Preferably, the plasticizer comprises polyether polyol and / or diisononyl hexahydrophthalate (DINCH).
[0049] More preferably, the plasticizer includes at least one of Dongda DL-400, DL-1000D, DL-2000D, DL-3000D, DL-4000D, and Hexamoll DINCH.
[0050] Preferably, the desiccant includes vinyltrimethoxysilane; more preferably, the desiccant includes Hubei New Blue Sky LH-171 and / or Union Carbide A171.
[0051] Preferably, the thixotropic agent comprises fumed silica; the fumed silica is surface treated with polydimethylsiloxane.
[0052] More preferably, the specific surface area of the fumed silica is 110 to 120 m2 / g.
[0053] More preferably, the thixotropic agent includes Cabot TS-720 and / or Hubei Huifu HB-151.
[0054] Preferably, the particle size of the heavy calcium carbonate is in the range of 10 to 50 μm, and the oil absorption value is in the range of 12 to 25 g / 100 g.
[0055] More preferably, the heavy calcium carbonate includes at least one of CC-200, CC-500, CC-800 and CC-1000 of Guangfu Building Materials.
[0056] Preferably, the surface of the nano calcium carbonate is modified by fatty acid; the crystal form is cubic crystal form; the specific surface area is 20 to 30 m 2 / g; oil absorption value ≤25g / 100g.
[0057] More preferably, the nano calcium carbonate includes Hubei Guoding Huaming SP200 and / or Jiangxi Bairui CCR-805.
[0058] Preferably, the component A comprises the following ingredients, measured by mass: 60-100 parts of silane-modified polyether resin, 0.1-5 parts of a first coupling agent, 0.5-10 parts of an antioxidant, 0-40 parts of a diluent, 0-50 parts of a plasticizer, 1-20 parts of an epoxy catalyst, 0.1-5 parts of a dehydrating agent, 1-20 parts of a thixotropic agent, 5-100 parts of heavy calcium carbonate, and 5-100 parts of nano calcium carbonate;
[0059] Calculated by weight, the B component includes the following ingredients: 10 to 100 parts of epoxy resin, 0.1 to 5 parts of a second coupling agent, 5 to 50 parts of a plasticizer, 0.1 to 5 parts of a dehydrating agent, 0.1 to 5 parts of an MS catalyst, 1 to 20 parts of a thixotropic agent, 0.01 to 5 parts of carbon black, 5 to 100 parts of heavy calcium carbonate, and 5 to 100 parts of nano calcium carbonate.
[0060] More preferably, the component A comprises the following ingredients by weight: 90-100 parts of silane-modified polyether resin, 2-4 parts of first coupling agent, 2-3 parts of antioxidant, 0-15 parts of plasticizer, 3-6 parts of epoxy catalyst, 0.5-2 parts of dehydrating agent, 6-10 parts of thixotropic agent, 30-50 parts of heavy calcium carbonate, and 30-50 parts of nano calcium carbonate.
[0061] More preferably, the B component includes the following ingredients, measured by mass: 30 to 50 parts of epoxy resin, 2 to 4 parts of a second coupling agent, 15 to 50 parts of a plasticizer, 0.5 to 2 parts of a dehydrating agent, 1 to 3 parts of an MS catalyst, 2 to 15 parts of a thixotropic agent, 0.03 to 0.1 parts of carbon black, 15 to 60 parts of heavy calcium carbonate, and 15 to 60 parts of nano calcium carbonate.
[0062] More preferably, the component A comprises the following ingredients by weight: 90-100 parts of silane-modified polyether resin, 3-4 parts of first coupling agent, 2-3 parts of antioxidant, 5-15 parts of plasticizer, 3-7 parts of epoxy catalyst, 0.5-2 parts of dehydrating agent, 6-10 parts of thixotropic agent, 30-50 parts of heavy calcium carbonate, and 30-50 parts of nano calcium carbonate.
[0063] More preferably, the B component includes the following ingredients, measured by mass: 40-50 parts of epoxy resin, 3-4 parts of second coupling agent, 40-50 parts of plasticizer, 0.8-2 parts of dewatering agent, 1-3 parts of MS catalyst, 10-15 parts of thixotropic agent, 0.03-0.1 parts of carbon black, 40-60 parts of heavy calcium carbonate, and 40-60 parts of nano calcium carbonate.
[0064] The two-component hybrid adhesive of the present invention has a component A that is a paste formed by mixing a silane-modified polyether resin (MS resin) as the main resin, and can be further supplemented with plasticizers, dewatering agents, coupling agents, epoxy catalysts and other auxiliary agents or inorganic fillers under vacuum; and a component B that is a paste formed by mixing an epoxy resin as the main resin, and can be further supplemented with plasticizers, dewatering agents, coupling agents, MS catalysts and other auxiliary agents or inorganic fillers under vacuum. After the two components AB are evenly mixed, the MS resin and the epoxy resin are blended to form an interpenetrating network structure through moisture curing of the MS resin and self-curing of the epoxy resin, and then the first coupling agent is used to react with the epoxy group to form a chemical bond, forming a chemical crosslink, thereby improving the mechanical properties and aging resistance of the two-component hybrid adhesive and improving the stability.
[0065] The second aspect of the present invention provides a method for preparing the two-component hybrid glue according to the first aspect of the present invention, comprising the following steps:
[0066] The components in component A and component B are mixed respectively to obtain component A and component B;
[0067] The obtained component A and component B are then mixed to obtain the two-component hybrid glue.
[0068] The third aspect of the present invention provides an adhesive, which includes the two-component hybrid adhesive according to the first aspect of the present invention.
[0069] The fourth aspect of the present invention provides a use of the two-component hybrid glue described in the first aspect of the present invention or the adhesive described in the third aspect of the present invention in the fields of automobiles, electrical appliances, electronics or construction.
[0070] The two-component hybrid adhesive of the present invention, after the two components AB are uniformly mixed, the MS resin and the epoxy resin are blended to form an interpenetrating network structure through moisture curing of the MS resin and self-curing of the epoxy resin, and a chemical bond is formed between the two components by adding an amino coupling agent, thereby forming an elastomer with excellent mechanical properties and aging resistance. While maintaining the flexibility of the MS resin, the high strength of the epoxy resin can also be taken into account. The adhesive can be used in the fields of rock slab pasting, ceramic tile pasting, etc., and has an excellent bonding effect.
[0071] Preferably, the two-component hybrid glue or adhesive is used in the field of construction.
[0072] More preferably, the two-component hybrid glue or adhesive is used for gluing rock slabs and / or ceramic tiles.
[0073] Compared with the prior art, the present invention has the following beneficial effects:
[0074] (1) The two-component hybrid adhesive of the present invention introduces a coupling agent containing an active group. Compared with the two-component coupling agent without the coupling agent, the aging resistance is improved. After long-term double 85 (85°C / 85% humidity) aging, the problem of powdering will not occur, which avoids the influence of powdering on the bonding effect, and the retention rate of tensile strength and elongation at break is high. At the same time, the initial mechanical properties of the two-component hybrid adhesive after curing are good.
[0075] (2) The two-component hybrid adhesive of the present invention can further improve the initial mechanical properties of the two-component hybrid adhesive by further introducing a specific antioxidant or adjusting the dosage of the coupling agent and the antioxidant, the tensile strength is increased to more than 5 MPa, the elongation at break is increased to more than 100%, and the tensile shear strength is increased to more than 5 MPa. Moreover, after aging for 1000 h at 85°C / 85% humidity, the tensile shear strength only decreases by less than 20%, and a good bonding effect can still be maintained.
[0076] (3) The two-component hybrid adhesive of the present invention has excellent initial mechanical properties and aging resistance, and can avoid the problem of powdering caused by long-term exposure to high temperature and high humidity conditions, which affects the bonding effect. It is suitable as an adhesive and is applied to the fields of automobiles, electrical appliances, electronics, construction, etc., especially the bonding of rock slabs and ceramic tiles. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 This is the free radical chain reaction process during aging of the two-component hybrid glue in the embodiment of the present invention.
[0078] Figure 2 This is a SEM image of the two-component hybrid glue in Example 1 of the present invention after being mixed and cured at a ratio of 2:1.
[0079] Figure 3 The tensile strength changes of the two-component hybrid rubber during aging in Example 1 and Comparative Examples 1-10 of the present invention.
[0080] Figure 4 The change of elongation at break during aging of the two-component hybrid adhesive in Example 1 and Comparative Examples 1-10 of the present invention.
[0081] Figure 5 The tensile shear strength changes of the two-component hybrid adhesives of Example 1 and Comparative Examples 1-10 during the aging process. DETAILED DESCRIPTION
[0082] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0083] Some of the raw materials used in the following examples and comparative examples of the present invention are described as follows:
[0084] MS resin (silane-modified polyether resin): SAX400, manufactured by Kaneka Chemical Co., Ltd. of Japan; viscosity (25° C.) is 24000 mPa·s.
[0085] Epoxy resin: GELR-128, Hongchang, epoxy equivalent 180-190 g / eq, viscosity (25°C) 12000-15000 mPa·s.
[0086] The first coupling agent: Dynasylan 1146, Evonik, contains two amino groups in its structure.
[0087] The second coupling agent: a silane coupling agent containing glycidyl ether (epoxy group), KBM-403, Shin-Etsu, Japan.
[0088] Polyphenol antioxidant: Antioxidant 1010, BASF.
[0089] Monophenol antioxidant: Antioxidant 1076, BASF.
[0090] Plasticizer: diisononyl hexahydrophthalate, Hexamoll DINCH.
[0091] Epoxy catalyst: tertiary amine catalyst, DMP-30.
[0092] MS catalyst: chelated tin catalyst, U-220H, Nitto Chemical.
[0093] Water removal agent: vinyl trimethoxysilane, LH-171, Hubei Xinlantian.
[0094] Thixotropic agent: hydrophobic fumed silica, surface treated with polydimethylsiloxane, with a specific surface area of 115m 2 / g, TS-720, Cabot.
[0095] Heavy calcium carbonate (heavy calcium carbonate): CC-500, Guangfu Building Materials; average particle size <28μm, oil absorption value 16~20g / 100g.
[0096] Nano calcium carbonate (nano calcium): SP200, Hubei Guoding Huaming; surface modified by fatty acid, cubic crystal form; specific surface area of 25±2m 2 / g, oil absorption value ≤25g / 100g.
[0097] The following is an explanation with reference to specific embodiments and comparative examples.
[0098] Example 1
[0099] This embodiment provides a two-component hybrid adhesive, including component A and component B. The specific formula is shown in Table 1.
[0100] The preparation method of the two-component hybrid glue in this embodiment includes the following steps:
[0101] Component A:
[0102] (1) Put MS resin and plasticizer into a reaction kettle and stir evenly;
[0103] (2) Add heavy calcium, nano calcium and thixotropic agent and stir evenly;
[0104] (3) Add antioxidant, stir evenly, start material dispersion, turn on the heating of the reactor, raise the temperature to 120° C., and start vacuuming at the same time, keep the temperature and pressure for 1 to 2 hours, while ensuring that the antioxidant is dissolved, remove water from the material;
[0105] (4) Maintain the pressure, turn off the heating device, and turn on the water cooling device of the equipment to cool the material until the material temperature drops below 50°C;
[0106] (5) Relieving the pressure, adding the epoxy catalyst, the water removing agent, and the first coupling agent in sequence, starting stirring and dispersing, and simultaneously starting vacuuming, and dispersing at high speed for 30 minutes under vacuum;
[0107] (6) Reduce the stirring speed and dispersion speed, maintain the pressure for 15 minutes, and perform degassing;
[0108] (7) Pressure relief and material packaging;
[0109] Component B:
[0110] (1) Add epoxy resin and plasticizer into a reaction kettle and stir evenly;
[0111] (2) Add heavy calcium, nano calcium, thixotropic agent and carbon black and stir evenly;
[0112] (3) Start material dispersion, turn on the heating of the reactor, raise the temperature to 120°C, and start vacuuming at the same time, keep the temperature and pressure for 1 to 2 hours to remove water from the material;
[0113] (4) Maintain the pressure, turn off the heating device, and turn on the water cooling device of the equipment to cool the material until the material temperature drops below 50°C;
[0114] (5) Relieving the pressure, adding the dehydrating agent, the second coupling agent, and the MS catalyst in sequence, starting stirring and dispersing, and simultaneously starting vacuuming, and dispersing at high speed for 30 minutes under vacuum;
[0115] (6) Reduce the stirring speed and dispersion speed, maintain the pressure for 15 minutes, and perform degassing;
[0116] (7) Pressure relief and material packaging;
[0117] When in use, component A and component B are mixed in a desired ratio to obtain a two-component hybrid glue.
[0118] Example 2
[0119] Example 2 provides a two-component hybrid adhesive. The differences from Example 1 are shown in Table 1; the preparation method is the same as that of Example 1.
[0120] Comparative Examples 1 to 10
[0121] Comparative Examples 1 to 10 provide a two-component hybrid adhesive, and the differences from Example 1 are shown in Table 1.
[0122] The preparation methods of the two-component hybrid adhesives of Comparative Examples 1 to 10 are the same as those of Example 1.
[0123] Table 1 Formula table of Examples 1 to 2 and Comparative Examples 1 to 10 (parts by mass)
[0124]
[0125]
[0126] The addition of polyphenol antioxidants, monophenol antioxidants, polyamino coupling agents (first coupling agents) and monoamino coupling agents in Examples 1 to 2 and Comparative Examples 1 to 10 are summarized in Table 2 below.
[0127] Table 2 Antioxidant and coupling agent addition in Examples 1 to 2 and Comparative Examples 1 to 10
[0128]
[0129]
[0130] Among them, “√” means added, and “×” means not added.
[0131] Performance Testing
[0132] Component A and component B of Example 1 and Comparative Examples 1 to 10 were weighed at a mass ratio of 1:1, and that of Example 2 was weighed at a mass ratio of 2:1. After uniform mixing, a two-component hybrid adhesive was formed, which was completely cured at room temperature for 7 days for subsequent performance testing.
[0133] Surface drying time: Test according to GB / T 13477.5-2002 Test methods for building sealing materials, Part 5, Determination of surface drying time.
[0134] Tensile strength and elongation at break: tested in accordance with GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber.
[0135] Tensile shear strength: refer to GBT 7124-2008 Determination of tensile shear strength of adhesives (rigid material to rigid material) for testing.
[0136] The test results of surface drying time, tensile strength, elongation at break and tensile shear strength are shown in Table 3.
[0137] Aging test:
[0138] (1) The two-component hybrid adhesive obtained in the examples and comparative examples was aged at 85°C and 85% humidity, and the tensile strength and elongation at break after aging were measured according to the above-mentioned tensile strength and elongation at break test standards. The results are as follows: Figure 3 and Figure 4 .
[0139] (2) Tensile shear strength: The two-component hybrid adhesives of the examples and comparative examples were aged at 85°C and 85% humidity, and the tensile shear strengths of the hybrid adhesives at different aging times were measured with reference to the determination of tensile shear strength of adhesives in GB / T 7124-2008 (the substrates were rigid materials, beech wood and anodized aluminum). The results were as follows: Figure 5 .
[0140] Table 3 Performance comparison table of Examples 1 to 2 and Comparative Examples 1 to 10
[0141]
[0142]
[0143] As can be seen from Table 1, the two-component curing adhesive obtained by the present invention has good mechanical properties by introducing a specific coupling agent containing an amino group. As can be seen from Examples 1 to 2 and Comparative Examples 4 to 10, the tensile strength of the obtained two-component hybrid adhesive is not less than 3.4 MPa, the elongation at break is not less than 61%, and the tensile shear strength is not less than 3.5 MPa; while Comparative Examples 1 to 3 lack the coupling agent containing an amino group, and their tensile strength does not exceed 3.1 MPa, the elongation at break does not exceed 53%, and the tensile shear strength is also relatively low.
[0144] Figure 1 This is the free radical chain reaction process of the two-component hybrid glue in the embodiment of the present invention during aging. Under the influence of external conditions such as strong light, high temperature or metal ions, MS resin and epoxy resin as polymer materials will undergo a series of chemical reactions, causing changes in the molecular structure, and ultimately causing the material to lose its use value. Among the many influencing factors, aging is the most important factor. External factors induce the generation of highly active free radicals, which are rapidly oxidized into peroxy radicals under the action of oxygen. Peroxy radicals react with RH to generate new carbon chain radicals, which accelerate the aging of the material, such as Figure 1 As shown. The present invention uses a specific hindered phenol antioxidant to improve aging resistance. Hindered phenol antioxidants are a class of compounds with substituted groups on one or both sides of the -OH on the benzene ring, and their structure generally includes two tert-butyl groups. Since the hydroxyl group is restricted by spatial barriers, the hydrogen atom (H) can easily fall off from the original molecular structure, thereby achieving the effect of donating protons and combining with peroxyl radicals (ROO-), alkyl radicals, hydroxyl radicals, etc., causing them to lose their original activity, resulting in the termination of the oxygen aging reaction.
[0145] Figure 2This is a SEM image of the two-component hybrid adhesive in Example 1 of the present invention after being mixed and cured in a ratio of 2:1. The two-component hybrid adhesive is obtained by mixing component A and component B in Example 1 in a mass ratio of 2:1. After normal curing, it can be observed under a scanning electron microscope that the two-component hybrid adhesive presents an island structure, where the "sea" is MS resin and the "island" is epoxy resin.
[0146] Figure 3 The tensile strength changes of the two-component hybrid rubber in Example 1 and Comparative Examples 1-10 during the aging process of the present invention. Figure 4 The elongation at break of the two-component hybrid adhesive during aging in Example 1 of the present invention and Comparative Examples 1 to 10 is shown in FIG. Figure 3 and Figure 4 It can be seen that:
[0147] The tensile strength of the two-component hybrid adhesive of Example 1 of the present invention decayed by about 20% when aged for 200 hours at 85°C and 85% humidity, and no obvious decay was observed in the subsequent aging; the elongation at break not only did not decay, but increased to a certain extent. It is inferred that this is because during the double 85 aging, the unreacted groups continued to react to form longer molecular chains. After the molecular chain length was increased, the strength would decay slightly, while the elongation would increase instead.
[0148] In Comparative Example 1, no antioxidant or coupling agent was added. After aging for 200 h at 85° C. and 85% humidity, the material was directly powdered and could not be further subjected to aging test.
[0149] Comparative Example 2 only added an alkylated polyphenol antioxidant, and Comparative Example 3 only added an alkylated monophenol antioxidant. At 85°C and 85% humidity, the tensile strength and elongation at break both showed continuous attenuation, and the attenuation amplitude was larger than that of Example 1. In comparison, the performance of the alkylated polyphenol antioxidant in Comparative Example 2 was better than that of the alkylated monophenol antioxidant in Comparative Example 3.
[0150] Comparative Example 4 only added a polyamino coupling agent, and Comparative Example 5 only added a monoamino coupling agent. At 85°C and 85% humidity, the tensile strength and elongation at break also showed continuous attenuation, and the attenuation amplitude was also larger than that of Example 1. In comparison, the performance of Comparative Example 4 only adding a polyamino coupling agent is better than that of Comparative Example 5 only adding a monoamino coupling agent.
[0151] Comparing Example 1 with Comparative Example 6, in which an alkylated monophenol antioxidant and a monoamino coupling agent are added, the aging resistance of Example 1 is significantly better than that of Comparative Example 6 at 85° C. and 85% humidity.
[0152] It can be seen from Comparative Examples 7 and 8 that when the amount of alkylated polyphenol antioxidant is small, although the initial mechanical properties after curing are similar to those of Example 1, the aging resistance attenuation is large, and the aging resistance is not as good as that of Example 1; when the amount of alkylated polyphenol antioxidant is large, the initial mechanical properties after curing are obviously not as good as that of Example 1. Although its aging resistance is worse than that of Comparative Example 7, it is still worse than that of Example 1, and the overall performance is not as good as that of Example 1.
[0153] In Comparative Examples 9 and 10, the dosage of the polyamino coupling agent (first coupling agent) was changed, and the initial mechanical properties of the two-component hybrid adhesive after curing were significantly inferior to those of Example 1, and the aging resistance was also inferior to that of Example 1.
[0154] Figure 5 The tensile shear strength changes of the two-component hybrid adhesives of Example 1 and Comparative Examples 1 to 10 during the aging process. Figure 5 It can be seen that after the two-component hybrid adhesive of Example 1 of the present invention decays by about 20% after aging for 400 hours at 85°C and 85% humidity, the tensile shear strength no longer decreases, that is, it still maintains excellent bonding performance after aging, and has good aging resistance and bonding strength. In the comparative examples, except for Comparative Example 7, the initial tensile shear strength is significantly lower than that of Example 1 of the present invention, and the bonding strength is poor. Although the initial tensile shear strength of Comparative Example 7 is close to that of Example 1, it has decayed by about 56% after aging for 200 hours, and the aging resistance is poor.
[0155] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A two-component hybrid adhesive, characterized in that: It includes component A and component B; The component A comprises a silane-modified polyether resin, a first coupling agent, an antioxidant, a first auxiliary agent, and a first inorganic filler; The B component includes epoxy resin, a second coupling agent, a second auxiliary agent, and a second inorganic filler; The first coupling agent has at least two active groups in its structure; the active groups include groups that can react with methoxy, ethoxy, epoxy or hydroxyl groups; the antioxidant includes hindered phenol antioxidants; the amount of the first coupling agent is 5 to 10% of the mass of the epoxy resin; the amount of the antioxidant is 1 to 4% of the total mass of the silane-modified polyether resin and the epoxy resin.
2. The two-component hybrid adhesive according to claim 1, characterized in that: The mass ratio of the A component to the B component is (1-5):
1.
3. The two-component hybrid adhesive according to claim 1, characterized in that: The first coupling agent contains 2 to 3 amino groups in its structure; and / or the second coupling agent includes a silane coupling agent containing an epoxy group.
4. The two-component hybrid adhesive according to claim 1, characterized in that: The hindered phenol antioxidant contains alkylated bisphenol or polyphenol in its structure.
5. The two-component hybrid adhesive according to claim 1 or 3, characterized in that: The silane-modified polyether resin includes a silane-modified polyether resin terminated by a dialkoxy group or a monoalkoxy group.
6. The two-component hybrid adhesive according to claim 1 or 2, characterized in that: The first auxiliary agent includes at least one of a diluent, a plasticizer, an epoxy catalyst, a water scavenger, and a thixotropic agent; And / or, the second auxiliary agent includes at least one of a plasticizer, a MS catalyst, a water scavenger, carbon black, and a thixotropic agent; And / or, the first inorganic filler and the second inorganic filler both include heavy calcium carbonate and / or nano calcium carbonate.
7. The two-component hybrid adhesive according to claim 6, characterized in that: The component A comprises the following ingredients by weight: 60 to 100 parts of silane-modified polyether resin, 0.5 to 10 parts of a first coupling agent, 0.1 to 5 parts of an antioxidant, 0 to 40 parts of a diluent, 0 to 50 parts of a plasticizer, 1 to 20 parts of an epoxy catalyst, 0.1 to 5 parts of a dehydrating agent, 1 to 20 parts of a thixotropic agent, 5 to 100 parts of heavy calcium carbonate, and 5 to 100 parts of nano calcium carbonate; The B component includes the following ingredients by weight: 10 to 100 parts of epoxy resin, 0.1 to 5 parts of the second coupling agent, 5-50 parts of plasticizer, 0.1-5 parts of water remover, 0.1-5 parts of MS catalyst, 1-20 parts of thixotropic agent, 0.01-5 parts of carbon black, 5-100 parts of heavy calcium carbonate, and 5-100 parts of nano calcium carbonate.
8. A method for preparing the two-component hybrid adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: The components in component A and component B are mixed respectively to obtain component A and component B; The obtained component A and component B are then mixed to obtain the two-component hybrid glue.
9. An adhesive, characterized in that: The adhesive comprises the two-component hybrid adhesive according to any one of claims 1 to 7.
10. Use of the two-component hybrid glue according to any one of claims 1 to 7 or the adhesive according to claim 9 in the fields of automobiles, electrical appliances, electronics or construction.
Citation Information
Cited By
A high-performance two-component hybrid adhesive for bonding and sealing new energy battery packs
CN122941335A